An examination of the challenges involved in distributing a strong and consistent destination image in the marketing of Tourism in Malaysia - Phang, Grace Ing; Liew, Janie Tsonis; Cheuk, Sharon Choy Sheung; Izyanti Awang Razli (The Clute Institute,Estelle van Tonder, Ph.D, 2010)
The future of marketing will be a battle of brands and destination branding is arguably the tourism industry’s biggest challenge (Pike, 2005). Marketing a destination consistently over time is critical to the success of destination marketing organisations (DMOs) and destination marketing companies (DMCs). However, media and market proliferation and clusterisation creates a high risk of contrary and confusing messages. This research paper reports on the findings of a two year study on the promotion of transportation in tourism development in Malaysia which examined the challenges involved in distributing a strong and consistent image of a destination. Key issues identified include the complexity of relationships which co-exist in the marketing of a tourism destination, its place image and conflicting messages. A qualitative approach to in-depth interviews was conducted with key respondents who were policy makers, tour and travel agents, non-government organisations, and residents in Malaysia. The empirical evidence has shown that policy makers in Government, although receptive to the promotion of tourism, are not entirely aware of the roles each is involved in the distribution of a strong and consistent image of place in the marketing of tourism in Malaysia